Gender features of depressive disorders in women - N. A. Tyuvina; V. V. Balabanova; E. O. Voronina (Неврология, нейропсихиатрия, психосоматика, 2015)
The authors give the data available in the literature and the results of their investigations of the gender features of depressive disorders in women. They analyze the results of studies relating to gender differences in the neurohormonal system from the embryonic period, as well as those in the lateralization of neuromorphofunctional provision of emotions. Based on their clinical observations, the authors discuss the varying roles of menopause in the etiopathogenesis of climacteric, psychogenic, and endogenous depression; in these forms of depression, menopause may be a cause, ground, or trigger, respectively. The influence of endocrine and sociopsychological factors on the development of postpartum depression is considered. The authors unveil the diagnostic and predictive value of premenopausal syndrome with depressive disorders at different stages of a depressive episode: the prediction of depression when depressive symptoms appear in the premenopausal period, as well as the reduction of premenopausal depressive disorders as evidence of intermission. Based on the data available in the literature, the authors consider the clinical features of depression in women: earlier onset; more frequent depressive episodes; greater presentation of atypical symptoms (anxiety, fatigue, increased appetite, weight gain, hypersomnia, and signs of somatization), as well as rarer suicidal tendencies as comparedto men. It is concluded that the gender features of depression in women are due to the whole complex of gender factors, such as neurophysiological, neuroendocrine, and sociopsychological ones.